2019
DOI: 10.1186/s13071-018-3276-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Cytauxzoon felis to domestic cats by Amblyomma americanum nymphs

Abstract: BackgroundSuccessful Cytauxzoon felis transmission studies have occurred using Amblyomma americanum adults acquisition-fed as nymphs on an experimentally infected domestic cat or Dermacentor variabilis adults fed as nymphs on a splenectomized bobcat. Here, we evaluated A. americanum and D. variabilis nymphs acquisition-fed as larvae on a C. felis-infected carrier domestic cat for competence to transmit the protozoan parasite as nymphs to naïve, healthy domestic cats.MethodsAmblyomma americanum and D. variabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 21 publications
0
23
2
Order By: Relevance
“…Acute cytauxzoonosis is one of the most fatal diseases in domestic cats, such that for a long time domestic cats were thought to have a minimal, if any, role in the enzootic maintenance of C. felis [ 11 , 18 , 32 ]. Over the past two decades, several prevalence studies have confirmed domestic cats as C. felis reservoirs [ 39 , 40 , 41 ] and experimentally demonstrated that domestic cats can serve as competent reservoirs for subsequent C. felis transmission by ticks, especially A. americanum [ 3 , 4 , 38 ]. C. felis -carrier surveys in states adjacent to Kansas have identified that 0.8–12.9% of domestic cats may be C. felis -carriers [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute cytauxzoonosis is one of the most fatal diseases in domestic cats, such that for a long time domestic cats were thought to have a minimal, if any, role in the enzootic maintenance of C. felis [ 11 , 18 , 32 ]. Over the past two decades, several prevalence studies have confirmed domestic cats as C. felis reservoirs [ 39 , 40 , 41 ] and experimentally demonstrated that domestic cats can serve as competent reservoirs for subsequent C. felis transmission by ticks, especially A. americanum [ 3 , 4 , 38 ]. C. felis -carrier surveys in states adjacent to Kansas have identified that 0.8–12.9% of domestic cats may be C. felis -carriers [ 39 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Successful transmission of infectious sporozoites requires transstadial maintenance of the parasite through larvae-to-nymph or nymph-to-adult ecdysis. In the U.S., competent biological transmission vectors for C. felis include the ixodid ticks Dermacentor variabilis (American dog tick) and Amblyomma americanum (Lone star tick) [ 2 , 3 , 4 , 5 ]. The geographic distribution of D. variabilis extends throughout the eastern half of the U.S. and in focal regions along the western coast [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Transstadial maintenance of the parasite through the larvae-to-nymph or nymph-to-adult ecdysis is required for the transmission of the infectious sporozoites to a new felid host during the subsequent tick bloodmeal. The competent biological transmission vectors of C. felis in the U.S. include Dermacentor variabilis (American dog tick) and Amblyomma americanum (Lone star tick) [ 2 , 3 , 4 , 5 ]. The range of D. variabilis encompasses the eastern U.S. as well as focal regions in the west [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because Theileria equi was until recently classified as Babesia equi , it may be phylogenetically closer to Babesia than other Theileria species, leading to the cross-reactivity observed in the Babesia genus-specific FISH test. Cytauxzoon felis is a tick-borne apicomplexan parasite that infects felids worldwide and causes severe disease among domestic cats in the US [ 22 ]. The ability of the Babesia genus-specific FISH test to differentiate B. felis from C. felis requires further investigation, because in silico analysis predicts that there may be a weak cross-recognition of C. felis .…”
Section: Discussionmentioning
confidence: 99%